Toxic chemicals : risk prevention through use reduction - Higgins, Thomas E., 1948-; Sachdev, Jayanti A.; Engleman, Stephen A. (Boca Raton, FL : CRC Press, 2011)
'Catastrophic events such as the Bhopal, India tragedy and rising incidences of cancer in areas neighboring industrial facilities have heightened concern over the use of toxic chemicals in manufacturing and industry. Based on the author's research conducted through their development of a program in Sao Paulo, Brazil, the book explores the history of toxic chemical release reporting programs, presents data on the actual toxicity of chemicals currently in use, discusses variables that contribute to the relative toxicity of a substance, compares alternate emphases in existing programs for reducing environmental threats, and provides a specific and health-based program to reduce or eliminate the use of toxic chemicals'--
Includes bibliographical references and index.
Keywords: Chemical industry -- Waste minimization; Hazardous wastes -- Management -- Government policy; Chemicals -- Accidents -- Prevention; LAW / Environmental; SCIENCE / Environmental Science; TECHNOLOGY & ENGINEERING / Manufacturing